The Economics of Liquid Staking Derivatives: Basis Determinants and Price Discovery - Stefan Scharnowski; Hossein Jahanshahloo (Journal of Futures Markets, 2024)
ABSTRACT This paper provides a first economic analysis of liquid staking tokens, which are derivatives representing a share of staked tokens in Proof-of-Stake blockchains. We document substantial time-variation in the “liquid staking basis” as given by the price difference between a derivative staking token and its underlying cryptocurrency. We find evidence that staking rewards, concentration risks, limits to arbitrage, and behavioral factors influence this basis. The liquid staking basis is wider when the yields offered by the liquid staking protocol are low relative to the alternative of staking directly, when cryptocurrency returns are more volatile, and when secondary market liquidity is low. In contrast, it is smaller when investors pay more attention to liquid staking and when investor sentiment is positive. Furthermore, liquid staking tokens contribute a significant and overall growing amount to price discovery in the underlying cryptocurrencies.
Keywords: 330; cryptocurrency; liquidity; price discovery; proof-of-stake; staking